2019
DOI: 10.3892/etm.2019.7707
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood miR‑372 as a biomarker for ulcerative colitis via direct targeting of NLRP12

Abstract: The present study aimed to investigate the expression pattern and underlying mechanism of microRNA-372 (miR-372) in the progression of ulcerative colitis (UC). Reverse transcription-quantitative polymerase chain reaction was used to measure miR-372 expression levels in the blood and colonic mucosa tissue samples from patients with UC. The present study demonstrated that levels of miR-372 were significantly increased in the blood and colonic mucosa tissue samples from patients with UC compared with healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…The remaining 305 full-text articles were screened and 188 were excluded according to the exclusion criteria. Finally, 117 primary articles of expression profile studies were included in the systematic review, of which 15 studies 9 , 18 31 about diagnostic accuracy were included in the meta-analysis ( Table 1 ). Thirty-one studies only reported altered miRNA expression using various high-throughput miRNA chips (Table S2), and 71 studies detected miRNA expression using qPCR or quantitative in situ hybridization (ISH) (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 305 full-text articles were screened and 188 were excluded according to the exclusion criteria. Finally, 117 primary articles of expression profile studies were included in the systematic review, of which 15 studies 9 , 18 31 about diagnostic accuracy were included in the meta-analysis ( Table 1 ). Thirty-one studies only reported altered miRNA expression using various high-throughput miRNA chips (Table S2), and 71 studies detected miRNA expression using qPCR or quantitative in situ hybridization (ISH) (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a high level of miR-372 in peripheral blood samples has proved to be a potential biomarker to screen patients with ulcerative colitis from healthy controls. 21 In human cancers, several miRNAs have been identified to be candidate biomarkers for noninvasive screening, such as miR-520f, miR-1290, and miR-21. [22][23][24] Recent researches suggest the potential role of several miRNAs in the pathogenesis of CAS, which may be involved in the evolution of carotid plaque toward growth, instability, and rupture.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, deregulated miR-NAs have been identified in the colonic tissues of patients with UC [66]. Since then, there have been several reports stating correlation of ncRNA expression between colonic tissues and peripheral blood or feces [67,68], and ncRNA expression is continuously investigated in feces or peripheral blood and its components. Several studies have reported distinct ncRNA expression in feces of IBD patients and healthy controls [69][70][71][72], and many studies have reported altered ncRNA expression in the peripheral blood of IBD patients [67,68,71,[73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92], although there are differences in the amount of deregulated ncRNAs and their diagnostic accuracy being reported.…”
Section: Mirnas and Noncoding Rnasmentioning
confidence: 99%
“…Since then, there have been several reports stating correlation of ncRNA expression between colonic tissues and peripheral blood or feces [67,68], and ncRNA expression is continuously investigated in feces or peripheral blood and its components. Several studies have reported distinct ncRNA expression in feces of IBD patients and healthy controls [69][70][71][72], and many studies have reported altered ncRNA expression in the peripheral blood of IBD patients [67,68,71,[73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92], although there are differences in the amount of deregulated ncRNAs and their diagnostic accuracy being reported. While some studies show unremarkable accuracy of ncRNAs in distinguishing between patients and healthy controls with receiver operating characteristics analysis showing an area under the curve (AUC) of 0.65-0.79 [80,84,86], others report really promising results with an AUC of 0.97-0.99 for miRNA pairs of miR-215/miR-30e-Dig Dis 2022;40:1-13 DOI: 10.1159/000515522 3p, miR-215/miR-145, and miR-203/miR-145 [81]; 0.94 for serum miR-372 [67]; 0.88 for fecal miR-223 [71]; and 0.91 for miR-874-3p in distinguishing between colonic Crohn's disease and UC.…”
Section: Mirnas and Noncoding Rnasmentioning
confidence: 99%